Networks in cell biology - Buchanan, M. (Mark), 1961- (Cambridge : Cambridge University Press, 2010)
'The science of complex biological networks is transforming research in areas ranging from evolutionary biology to medicine. This is the first book on the subject, providing a comprehensive introduction to complex network science and its biological applications. With contributions from key leaders in both network theory and modern cell biology, this book discusses the network science that is increasingly foundational for systems biology and the quantitative understanding of living systems. It surveys studies in the quantitative structure and dynamics of genetic regulatory networks, molecular networks underlying cellular metabolism, and other fundamental biological processes. The book balances empirical studies and theory to give a unified overview of this interdisciplinary science. It is a key introductory text for graduate students and researchers in physics, biology and biochemistry, and presents ideas and techniques from fields outside the reader's own area of specialization'--Provided by publisher.
'Biologists now have access to a virtually complete map of all the genes in thehuman genome, and in the genomes of many other species. They are aggressivelyassembling a similarly detailed knowledge of the proteome, the full collection ofproteins encoded by those genes, and the transcriptome, the diverse set of mRNA'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Cellular control mechanisms; Biological systems; System analysis